2006
DOI: 10.1128/aac.00103-06
|View full text |Cite
|
Sign up to set email alerts
|

Heteroresistance to Colistin in Multidrug-Resistant Acinetobacter baumannii

Abstract: Multidrug-resistant Acinetobacter baumannii has emerged as a significant clinical problem worldwide and colistin is being used increasingly as "salvage" therapy. MICs of colistin against A. baumannii indicate its significant activity. However, resistance to colistin in A. baumannii has been reported recently. Clonotypes of 16 clinical A. baumannii isolates and ATCC 19606 were determined by pulsed-field gel electrophoresis (PFGE), and colistin MICs were measured. The time-kill kinetics of colistin against A. ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
427
3
18

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 498 publications
(471 citation statements)
references
References 35 publications
12
427
3
18
Order By: Relevance
“…Several investigators have reported heteroresistance to colistin in A. baumannii, which has been supposed to cause the emergence of colistin resistance by exposure to colistin [68][69][70]. Heteroresistance is generally defined as a case in which subpopulations of antibiotic-susceptible bacteria show resistance to certain antibiotics [71].…”
Section: Colistin Dependencementioning
confidence: 99%
“…Several investigators have reported heteroresistance to colistin in A. baumannii, which has been supposed to cause the emergence of colistin resistance by exposure to colistin [68][69][70]. Heteroresistance is generally defined as a case in which subpopulations of antibiotic-susceptible bacteria show resistance to certain antibiotics [71].…”
Section: Colistin Dependencementioning
confidence: 99%
“…Heteroresistance, which may be defined as a phenotypic manifestation of resistance within a genetically homogeneous strain 10 , has only rarely been described in Gram-negative bacteria [6][7][8][9] . Although authors are not certain about the clinical impact of this resistance phenotype in Gramnegative rods, our report suggests that heteroresistance may adversely affect the outcome of patients, since the A. baumannii isolate was recovered from the blood of a patient receiving meropenem therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, pulmonary infections do not always respond well to such systemic therapy, due to insufficient drug diffusion into pulmonary tissue and lume [8]. Bacteria that have persisted over treatment may develop resistance, but higher drug doses to compensate for poor diffusion may lead to systemic toxicity.…”
Section: New Theoretical Backgroundmentioning
confidence: 99%